Sistem Informasi Akuntansi Atas Siklus Pendapatan Pada Pratama Expressindo - Nadhilah Nur Rahmatina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to analyze the accounting information system for the revenue cycle at Pratama Expressindo using research methodology using qualitative methods. The data collection techniques used were interviews and observations. The results showed that the related functions in Pratama Expressindo all services are efficient but lack discipline, especially in the accounting department. There are no clear rules for accounting that affect performance. In the company's accountant system, there are two main functions, namely the administrative part as the part responsible for managing the company, while the finance department as the collection and management of income and expenditure in the company. Pratama Expressindo's accounting information system is well maintained, but there are areas that need improvement, such as improving customer payment processing. The use of information systems at Pratama Expressindo still uses a simple system and there are still many shortcomings, which initially did not use accounting software and now use accounting software.